A scoping review of ethical aspects of public-private partnerships in digital health - Marieke A. R. Bak; Daan Horbach; Alena Buyx; Stuart McLennan (npj Digital Medicine)
Abstract Partnerships between public and private organizations in digital health can promote more accessible, affordable, and high-quality care, but they also raise ethical and governance challenges. We searched PubMed, EMBASE, and Web of Science, identifying 46 studies examining ethical aspects of digital health public-private partnerships (PPPs). Three key themes emerged: data privacy and consent, ensuring public benefit and access, and good governance and demonstrating trustworthiness. We provide recommendations for each theme. To foster responsible innovation, we conclude that early and contextual operationalisation of ethics guidelines in PPPs is necessary to balance respect for fundamental values with the pursuit of impactful innovation. If PPPs become more successful as a result, this contributes to reducing the research waste of failed collaborations. Further research should clarify the scope of PPPs and definition of ‘public benefit’, and we call for critical study on the ‘economization’ of digital health promoted by public and private sector organizations.